A method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system
By using an iron-based phosphine-containing catalytic system, the problem of poor stability of the existing iron-based metal boron-containing catalytic system is solved, and the production of low-catalyst 1,4 structure polyconjugated dienes is achieved. The product has higher structural content and performance indicators, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202211620145.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The existing iron-based metal boron-containing catalytic system used to catalyze conjugated diene polymerization has problems such as poor stability, expensiveness and poor solubility, resulting in low polymerization yield and uncertain product structure and performance.
The iron-based phosphine-containing catalytic system was adopted, and polymerization was carried out by adding N,N-bidentate iron carboxylate catalyst, alkyl aluminum, phosphine compounds, conjugated dienes and solvents under anhydrous and oxygen-free conditions, followed by adding quenching agents and anti-aging agents, washed and dried in vacuo to obtain a low 1,4 structure polyconjugated diene.
It significantly improves catalytic stability and improves polymerization yield. The 3,4(1,2) structure content of the product reaches more than 65%, the glass transition temperature is increased to around 0℃, and the molecular chain binding energy is higher, making it suitable for industrial applications.
Smart Images

Figure CN115850546B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic polymerization of conjugated dienes, and in particular relates to a method for preparing low 1,4 structure polyconjugated dienes by using an iron-based phosphine-containing catalyst system. Background Art
[0002] 3,4 Polyisoprene rubber has gradually attracted widespread attention and research in recent years due to its excellent anti-skid performance, low rolling resistance and wear resistance brought by its high degree of branching.
[0003] Ritter and colleagues introduced a class of iron catalysts based on iminopyridine complexes, which used two different types of iminopyridine iron (II) complexes, combined with trialkylaluminum alkylating agents and boron co-catalysts, to effectively catalyze the polymerization of isoprene (Angew. Chem., Int. Ed. 2012, 51, 11805-11808). On this basis, Ricci et al. found that the imine part of the iminopyridine skeleton can adjust the selectivity of monomer insertion, which provides the possibility of regulating the microstructure of the polymer and producing low 1,4-structure polyisoprene (Macromolecules 2021, 54, 21, 9947–9959). However, the metal center of the iron-based catalyst has weak Lewis acidity, which is not conducive to the coordination insertion of the monomer, resulting in a low polymer yield of only about 40%. In order to solve this problem, relevant research at home and abroad has begun to use dealkylation reagents to improve the stability of the metal center, the most important of which is [Ph3C] + [B(CF5)4] - . In addition, B(C6F5)3 can also play a similar role. However, the above two boron-based dealkylation agents have prominent problems: high price, poor solubility, and the molecular weight distribution of the product using the B(C6F5)3 catalytic system is not single-peaked. The specific catalytic mechanism is still unclear, and the structure and performance of the product cannot be determined more accurately. Therefore, in order to make up for the above defects, it is urgent to develop a new catalytic system. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problems of poor central stability, high price and poor solubility of the existing iron-based metal boron-containing catalyst system for catalyzing the polymerization of conjugated dienes, and to provide a method for preparing low-1,4-structure polyconjugated dienes using an iron-based phosphine-containing catalyst system.
[0005] One of the purposes of the present invention is to provide a method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system, the method being carried out according to the following steps:
[0006] Under anhydrous and oxygen-free conditions, an N,N-bidentate carboxylic acid iron catalyst, alkyl aluminum, phosphine compound, conjugated diene and solvent are added to a reactor, and a polymerization reaction is carried out at 0-100° C. for 10-120 minutes by stirring. After the reaction, a quencher and an antioxidant are added, and the mixture is washed and vacuum dried to a constant weight to obtain a low 1,4 structure polyconjugated diene.
[0007] It is further defined that the N,N-bidentate iron carboxylate catalyst is any one of the following structural formulas:
[0008]
[0009] It is further defined that the phosphine compound is any one of the following structural formulas:
[0010]
[0011] It is further defined that the molar ratio of the conjugated diene to the iron element in the N,N-bidentate iron carboxylate catalyst is (5000-50000):1.
[0012] It is further defined that the molar ratio of the aluminum element in the alkyl aluminum to the iron element in the N,N-bidentate iron carboxylate catalyst is (1-100):1.
[0013] It is further defined that the molar ratio of phosphorus in the phosphine compound to iron in the N,N-bidentate iron carboxylate catalyst is (0.1-20):1.
[0014] It is further defined that the conjugated diene is one or a mixture of any ratio of isoprene, butadiene, β-farnesene and myrcene.
[0015] In a further embodiment, the solvent is a non-polar solvent.
[0016] It is further defined that the non-polar solvent is one or a mixture of any proportion of cyclohexane, n-hexane, petroleum ether, toluene and xylene.
[0017] It is further defined that the volume ratio of the conjugated diene to the solvent is 1:(1-20).
[0018] It is further defined that the quenching agent is a mixed solution of concentrated hydrochloric acid and methanol, wherein the volume ratio of methanol to concentrated hydrochloric acid is 50:1.
[0019] It is further defined that the antioxidant is an ethanol solution of 2,6-di-tert-butyl-4-methylphenol with a mass concentration of 1%.
[0020] It is further defined that the volume ratio of the antioxidant to the solvent is 1:25.
[0021] The second object of the present invention is to provide a low 1,4 structure polyconjugated diene prepared by the above method, wherein the number average molecular weight of the low 1,4 structure polyconjugated diene is 35,000-2 million g / mol, the molecular weight distribution is 1.5-5.0, the molar content of the 3,4 (1,2)-structure is 65-80%, the molar content of the 1,4-structure is 20-35%, and the glass transition temperature is -80-10°C.
[0022] The third object of the present invention is to provide an application of the low 1,4 structure polyconjugated diene prepared by the above method, which is used for preparing automobile tires.
[0023] Compared with the prior art, the present invention has the following significant effects:
[0024] 1) The present invention uses a nucleophilic phosphine compound as the third component in the catalyst system, which is easy to form a phosphorus-metal bond with a transition metal, and then form a relatively stable metal complex, thereby significantly improving the catalytic stability. At the same time, the phosphine compound used in the present invention has good solubility in non-polar solvents. Compared with other existing catalyst systems, the iron-based catalyst system with the participation of the phosphine compound can maintain efficient synergistic effects within a wider reaction temperature range, has excellent catalytic effect, moderate reaction speed, and good thermal stability.
[0025] 2) The catalytic system of the present invention can achieve the production of high 3,4 (1,2) polyconjugated diene, and the 3,4 structure content of the product of the system containing B (C6F5) 3 does not exceed 60%. In contrast, the 3,4 (1,2) structure content in the catalytic system of the present invention exceeds 65%, and the glass transition temperature of the product is around 0°C, which is significantly higher than the glass transition temperature of other system products of about -30°C. This means that the internal binding energy of the molecular chain of the product of the catalytic system of the present invention is higher, and the molecular chain is less likely to be destroyed, thereby enabling more flexible industrial applications.
[0026] 3) The present invention introduces phosphine compounds into the iron-based catalyst system for the first time and uses them to catalyze the polymerization of conjugated dienes. As the third component, it plays a key role in stabilizing the metal active center, can reduce the electron cloud density of the metal center, thereby facilitating the insertion of the monomer and achieving complete conversion of the monomer, thus solving the problem of poor stability of the current iron-based catalyst system and low yield of the obtained polymerization product. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The polyisoprene obtained in Example 1 1 H NMR spectrum;
[0028] Figure 2 This is the GPC spectrum of the polyisoprene obtained in Example 1;
[0029] Figure 3 This is the DSC spectrum of the polyisoprene obtained in Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0032] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0033] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.
[0034] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0035] Example 1: A method for preparing low-1,4-structure polyisoprene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0036] Under argon atmosphere, anhydrous cyclohexane (100 mL), isoprene (6.8 g, 100.0 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst Ⅰ (6.7 mg, 10 μmol), phosphine compound Ⅰ (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the polymerization was carried out at 30° C. for 120 min. 4 mL of 1% mass concentration of 2,6-di-tert-butyl-4-methylphenol ethanol solution was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After discarding the clear liquid, the polymer was washed three times with ethanol, and the obtained polymer was placed at 40° C. and vacuum dried to constant weight to obtain a polyisoprene elastomer.
[0037] Results: Yield: >99%, number average molecular weight (M n ):5.9×10 5 g / mol, molecular weight distribution (PDI): 2.7. Molar content of different structures: 1,4-structure accounts for 30%, 3,4-structure accounts for 70%, and the glass transition temperature is 2.1℃.
[0038] The obtained polyisoprene elastomer 1 H NMR spectra, GPC spectra and DSC spectra are shown in Figure 1-3 As shown, Figure 3 Example 1 Glass transition temperature of polyisoprene: starting point: -1.5°C, midpoint: 2.1°C, inflection point: 5.3°C, end point: 6.4°C, specific heat change * :0.344 / (g*K).
[0039] The information of the polyisoprene obtained in this example is shown in Tables 1-3.
[0040] Table 1 Molecular weight information
[0041] Peak <![CDATA[M p (g / mol)]]> <![CDATA[M n (g / mol)]]> <![CDATA[M w (g / mol)]]> <![CDATA[M z (g / mol)]]> <![CDATA[M z+1 (g / mol)]]> <![CDATA[M v (g / mol)]]> PD Peak1 1226551 586674 1556607 2887919 4338964 2685975 2.653
[0042] Table 2 Peak information table
[0043] Start(mins) End(mins) Baselineregion1 3.05833 4.05000 Baselineregion2 13.92500 14.37500 Peak1 5.74167 7.71667
[0044] Table 3 Peak trace information table
[0045] Peak Trace PeakMaxRT(mins) Peak Area (mV.s) Peak Height(mV) Peak1 RI 6.48333 157253.589 2903.183
[0046] Example 2: This example is different from Example 1 in that the amount of phosphine compound I used is (15.8 mg, 50 μmol), and the other steps and parameters are the same as those in Example 1.
[0047] Results: Yield: >99%, number average molecular weight (M n):8.7×10 5 g / mol, molecular weight distribution (PDI): 2.5. Molar content of different structures: 1,4-structure accounts for 31%, 3,4-structure accounts for 69%. Glass transition temperature is -0.2℃.
[0048] Example 3: This example is different from Example 1 in that the phosphine compound is phosphine compound II, the amount used is (3.2 mg, 10 μmol), the amount of anhydrous cyclohexane used is 50 mL, and the other steps and parameters are the same as in Example 1.
[0049] Results: Yield: 97%, number average molecular weight (M n ):4.5×10 5 g / mol, molecular weight distribution (PDI): 2.5. Molar content of different structures: 1,4-structure accounts for 35%, 3,4-structure accounts for 65%. Glass transition temperature is 3.1℃.
[0050] Example 4: This example is different from Example 1 in that the phosphine compound is phosphine compound II, the amount used is (6.4 mg, 20 μmol), the amount of anhydrous cyclohexane used is 50 mL, and the other steps and parameters are the same as in Example 1.
[0051] Results: Yield: >99%, number average molecular weight (M n ):3.5×10 5 g / mol, molecular weight distribution (PDI): 2.4. Molar content of different structures: 1,4-structure accounts for 35%, 3,4-structure accounts for 65%. Glass transition temperature is -10.3℃.
[0052] Example 5: This example is different from Example 1 in that the phosphine compound is phosphine compound III, the amount used is (2.7 mg, 10 μmol), and the other steps and parameters are the same as those in Example 1.
[0053] Results: Yield: >99%, number average molecular weight (M n ):5.8×10 5 g / mol, molecular weight distribution (PDI): 2.3. Molar content of different structures: 1,4-structure accounts for 28%, 3,4-structure accounts for 72%. Glass transition temperature is -9.7℃.
[0054] Example 6: This example is different from Example 1 in that the phosphine compound is phosphine compound III, the amount used is (13.5 mg, 50 μmol), and the other steps and parameters are the same as those in Example 1.
[0055] Results: Yield: >99%, number average molecular weight (M n ):8.5×10 5g / mol, molecular weight distribution (PDI): 2.1. Molar content of different structures: 1,4-structure accounts for 28%, 3,4-structure accounts for 72%. Glass transition temperature is -0.5℃.
[0056] Example 7: This example is different from Example 1 in that the phosphine compound is phosphine compound IV, the amount used is (2.8 mg, 10 μmol), and the other steps and parameters are the same as those in Example 1.
[0057] Results: Yield: >99%, number average molecular weight (M n ):9.0×10 5 g / mol, molecular weight distribution (PDI): 2.3. Molar content of different structures: 1,4-structure accounts for 31%, 3,4-structure accounts for 69%. Glass transition temperature is 4.5℃.
[0058] Example 8: This example is different from Example 1 in that the phosphine compound is phosphine compound IV, the amount used is (14.0 mg, 50 μmol), and the other steps and parameters are the same as those in Example 1.
[0059] Results: Yield: >99%, number average molecular weight (M n ):9.0×10 5 g / mol, molecular weight distribution (PDI): 2.3. Molar content of different structures: 1,4-structure accounts for 33%, 3,4-structure accounts for 67%. Glass transition temperature is -1.1℃.
[0060] Example 9: This example is different from Example 1 in that the phosphine compound is phosphine compound V, the amount used is (4.7 mg, 10 μmol), and the other steps and parameters are the same as those in Example 1.
[0061] Results: Yield: >99%, number average molecular weight (M n ):5.8×10 5 g / mol, molecular weight distribution (PDI): 2.4. Molar content of different structures: 1,4-structure accounts for 27%, 3,4-structure accounts for 73%. Glass transition temperature is -0.3℃.
[0062] Example 10: This example is different from Example 1 in that the phosphine compound is phosphine compound VI, the amount used is (5.3 mg, 10 μmol), and the other steps and parameters are the same as those in Example 1.
[0063] Results: Yield: >99%, number average molecular weight (M n ):4.6×10 5g / mol, molecular weight distribution (PDI): 2.3. Molar content of different structures: 1,4-structure accounts for 35%, 3,4-structure accounts for 65%. Glass transition temperature is -0.3℃.
[0064] Example 11: This example is different from Example 1 in that the phosphine compound is phosphine compound VII, the amount used is (6.7 mg, 10 μmol), and the other steps and parameters are the same as those in Example 1.
[0065] Results: Yield: >99%, number average molecular weight (M n ):5.5×10 5 g / mol, molecular weight distribution (PDI): 4.3. Molar content of different structures: 1,4-structure accounts for 32%, 3,4-structure accounts for 68%. Glass transition temperature is 3.3℃.
[0066] Example 12: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst II, and the amount used is (6.4 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0067] Results: Yield: >99%, number average molecular weight (M n ):8.0×10 5 g / mol, molecular weight distribution (PDI): 2.7. Molar content of different structures: 1,4-structure accounts for 25%, 3,4-structure accounts for 75%. Glass transition temperature is -0.8℃.
[0068] Example 13: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst III, and the amount used is (6.7 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0069] Results: Yield: 90%, number average molecular weight (M n ):4.2×10 5 g / mol, molecular weight distribution (PDI): 3.7. Molar content of different structures: 1,4-structure accounts for 30%, 3,4-structure accounts for 70%. Glass transition temperature is -0.7℃.
[0070] Example 14: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst IV, the amount used is (6.7 mg, 10 μmol), and the other steps and parameters are the same as in Example 1.
[0071] Results: Yield: 92%, number average molecular weight (M n ):3.5×10 5g / mol, molecular weight distribution (PDI): 2.3. Molar content of different structures: 1,4-structure accounts for 28%, 3,4-structure accounts for 72%. Glass transition temperature is 1.0℃.
[0072] Example 15: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst V, and the amount used is (5.6 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0073] Results: Yield: 96%, number average molecular weight (M n ):6.5×10 5 g / mol, molecular weight distribution (PDI): 2.0. Molar content of different structures: 1,4-structure accounts for 27%, 3,4-structure accounts for 73%. Glass transition temperature is 1.6℃.
[0074] Example 16: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst VI, and the amount used is (5.8 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0075] Results: Yield: >99%, number average molecular weight (M n ):4.0×10 5 g / mol, molecular weight distribution (PDI): 3.7. Molar content of different structures: 1,4-structure accounts for 34%, 3,4-structure accounts for 66%. Glass transition temperature is -15.5℃.
[0076] Example 17: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst Ⅶ, and the amount used is (5.9 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0077] Results: Yield: >99%, number average molecular weight (M n ):4.3×10 5 g / mol, molecular weight distribution (PDI): 2.5. Molar content of different structures: 1,4-structure accounts for 33%, 3,4-structure accounts for 67%. Glass transition temperature is -13.2℃.
[0078] Example 18: This example is different from Example 1 in that the N,N-bidentate iron carboxylate catalyst is N,N-bidentate iron carboxylate catalyst VIII, and the amount used is (5.9 mg, 10 μmol). The other steps and parameters are the same as those in Example 1.
[0079] Results: Yield: >99%, number average molecular weight (M n ):4.1×10 5g / mol, molecular weight distribution (PDI): 2.0. Molar content of different structures: 1,4-structure accounts for 35%, 3,4-structure accounts for 65%. Glass transition temperature is -10.8℃.
[0080] Example 19: A method for preparing low 1,4-structure polybutadiene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0081] Under argon atmosphere, anhydrous cyclohexane (100 mL), butadiene (5.4 g, 100 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst Ⅰ (6.7 mg, 10 μmol), phosphine compound Ⅰ (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the polymerization was carried out at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After the clear liquid was poured off, the polymer was washed three times with ethanol, and the obtained polymer was placed at 40° C. and vacuum dried to constant weight to obtain a polybutadiene elastomer.
[0082] Results: Yield: >99%, number average molecular weight (M n ):4.5×10 5 g / mol, molecular weight distribution (PDI): 2.0. Molar content of different structures: 1,4-structure accounts for 32%, 1,2-structure accounts for 68%. Glass transition temperature is -3.2℃.
[0083] Example 20: A method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0084] Under argon atmosphere, anhydrous cyclohexane (100 mL), butadiene (1.62 g, 30 mmol), isoprene (4.76 g, 70 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst I (6.7 mg, 10 μmol), and phosphine compound I (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the mixture was polymerized at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After the clear liquid was discarded, the polymer was washed three times with ethanol, and the obtained polymer was dried in vacuo at 40° C. to constant weight to obtain an isoprene-butadiene copolymer elastomer.
[0085] Results: Yield: >99%, number average molecular weight (Mn ):4.4×10 5 g / mol, molecular weight distribution (PDI): 3.0. The molar content of polyisoprene in isoprene-butadiene copolymer is 67%, of which 1,4-structure accounts for 30%, 3,4-structure accounts for 70%, and the molar content of polybutadiene accounts for 33%, of which 1,4-structure accounts for 26%, and 1,2-structure accounts for 74%. The glass transition temperature is -0.2℃.
[0086] Example 21: A method for preparing low 1,4 structure poly-β-farnesene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0087] Under argon atmosphere, anhydrous cyclohexane (100 mL), β-farnesene (20.4 g, 100 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst Ⅰ (6.7 mg, 10 μmol), and phosphine compound Ⅰ (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the polymerization was carried out at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After discarding the clear liquid, the polymer was washed three times with ethanol, and the obtained polymer was placed at 40° C. and vacuum dried to constant weight to obtain a polyβ-farnesene elastomer.
[0088] Results: Yield: >99%, number average molecular weight (M n ):5.7×10 5 g / mol, molecular weight distribution (PDI): 1.7. Molar content of different structures: 1,4-structure accounts for 34%, 3,4-structure accounts for 66%. Glass transition temperature is -7.4℃.
[0089] Example 22: A method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0090] Under argon atmosphere, anhydrous cyclohexane (100 mL), β-farnesene (6.12 g, 30 mmol), isoprene (4.76 g, 70 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst I (6.7 mg, 10 μmol), and phosphine compound I (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the mixture was polymerized at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After discarding the clear liquid, the polymer was washed three times with ethanol, and the obtained polymer was dried in vacuo at 40° C. to constant weight to obtain a β-farnesene-isoprene copolymer elastomer.
[0091] Results: Yield: 96%, number average molecular weight (M n ):5.4×10 5 g / mol, molecular weight distribution (PDI): 2.2. The molar content of polyisoprene in β-farnesene-isoprene copolymer is 69%, of which 1,4-structure accounts for 33% and 3,4-structure accounts for 67%; the molar content of polyfarnesene accounts for 31%, of which 1,4-structure accounts for 32% and 3,4-structure accounts for 68%. The glass transition temperature is -10.2℃.
[0092] Example 23: A method for preparing low-1,4-structure poly-β-myrcene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0093] Under an argon atmosphere, anhydrous cyclohexane (100 mL), β-myrcene (13.7 g, 100 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst Ⅰ (6.7 mg, 10 μmol), and phosphine compound Ⅰ (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the mixture was polymerized at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After the clear liquid was discarded, the polymer was washed three times with ethanol, and the obtained polymer was placed at 40° C. and dried in vacuum to constant weight to obtain a poly-β-myrcene elastomer.
[0094] Results: Yield: 97%, number average molecular weight (M n ):8.4×10 5 g / mol, molecular weight distribution (PDI): 2.6. Molar content of different structures: 1,4-structure accounts for 35%, 3,4-structure accounts for 65%. Glass transition temperature is 7.2℃.
[0095] Example 24: A method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system in this example is carried out by the following steps:
[0096] Under argon atmosphere, anhydrous cyclohexane (100 mL), β-myrcene (4.11 g, 30 mmol), isoprene (4.76 g, 70 mmol), triisobutylaluminum (79.3 mg, 0.4 mmol), N,N-bidentate carboxylic acid iron catalyst I (6.7 mg, 10 μmol), and phosphine compound I (3.2 mg, 10 μmol) were added to a 250 mL Schlenk tube in sequence, and the mixture was polymerized at 30° C. for 120 min. 4 mL of 1% ethanol solution of 2,6-di-tert-butyl-4-methylphenol was added, and then the reaction was terminated with a mixed solution of concentrated hydrochloric acid and methanol (the volume ratio of methanol to concentrated hydrochloric acid was 50:1). After the clear liquid was discarded, the polymer was washed three times with ethanol, and the obtained polymer was placed at 40° C. and dried in vacuum to constant weight to obtain a β-myrcene-isoprene copolymer elastomer.
[0097] Results: Yield: 98%, number average molecular weight (M n ):7.4×10 5 g / mol, molecular weight distribution (PDI): 2.5. The molar content of polyisoprene in β-myrcene-isoprene copolymer is 65%, of which 1,4-structure accounts for 35% and 3,4-structure accounts for 65%; the molar content of polymyrcene accounts for 35%, of which 1,4-structure accounts for 34% and 3,4-structure accounts for 66%. The glass transition temperature is -1.2℃.
[0098] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing low 1,4 structure polyconjugated diene using an iron-based phosphine-containing catalyst system, characterized in that: The method proceeds as follows: Under anhydrous and oxygen-free conditions, an N,N-bidentate carboxylic acid iron catalyst, alkyl aluminum, phosphine compound, conjugated diene and solvent are added to a reactor, and a polymerization reaction is carried out at 0-100° C. for 10-120 minutes by stirring. After the reaction is completed, a quencher and an anti-aging agent are added, and the mixture is washed and vacuum dried to a constant weight to obtain a low 1,4 structure polyconjugated diene; The N,N-bidentate iron carboxylate catalyst is any one of the following structural formulas: The phosphine compound is any one of the following structural formulas:
2. The method according to claim 1, characterized in that: The molar ratio of the conjugated diene to the iron element in the N,N-bidentate iron carboxylate catalyst is (5000-50000):1, the molar ratio of the aluminum element in the alkyl aluminum to the iron element in the N,N-bidentate iron carboxylate catalyst is (1-100):1, and the molar ratio of the phosphorus element in the phosphine compound to the iron element in the N,N-bidentate iron carboxylate catalyst is (0.1-20):
1.
3. The method according to claim 1, characterized in that The conjugated diene is one or a mixture of isoprene, butadiene, β-farnesene and myrcene, and the solvent is a non-polar solvent.
4. The method according to claim 3, characterized in that The non-polar solvent is one or a mixture of cyclohexane, n-hexane, petroleum ether, toluene and xylene.
5. The method according to claim 1, characterized in that The volume ratio of the conjugated diene to the solvent is 1:(1-20).
6. The method according to claim 1, characterized in that The quencher is a mixed solution of concentrated hydrochloric acid and methanol, wherein the volume ratio of methanol to concentrated hydrochloric acid is 50:1; the antioxidant is an ethanol solution of 2,6-di-tert-butyl-4-methylphenol with a mass concentration of 1%, and the volume ratio of the antioxidant to the solvent is 1:
25.
7. The low 1,4 structure polyconjugated diene prepared by the method according to any one of claims 1 to 6, characterized in that: The low 1,4 structure polyconjugated diene has a number average molecular weight of 35,000-2,000,000 g / mol, a molecular weight distribution of 1.5-5.0, wherein the molar content of 3,4(1,2)-structure is 65-80%, the molar content of 1,4-structure is 20-35%, and the glass transition temperature is -80°C to 10°C.
8. The low 1,4 structure polyconjugated diene obtained by the method according to any one of claims 1 to 6 is used for preparing automobile tires.
Citation Information
Patent Citations
Iron series ultrahigh molecular weight poly conjugate alkene, and preparation method thereof
CN110396150A
Polar conjugated olefin polymer as well as preparation method and application thereof
CN114805685A